Vascularized Composite Allotransplantation: Basic Research and Clinical Experience at Chang Gung - Huang, Ren-Wen; Anggelia, Madonna Rica; Cheng, Hui-Yun; Wei, Fu-Chan; Lin, Cheng-Hung (Seminars in Plastic Surgery, 2025)
Vascularized composite allotransplantation (VCA) represents one of the most complex frontiers in reconstructive surgery, requiring simultaneous transfer of multiple tissue types, including skin, muscle, bone, and nerves. Success depends on the multidisciplinary integration of immunology, surgery, rehabilitation, and psychology. Chang Gung Memorial Hospital has established itself as a pioneer in clinical VCA in Taiwan, contributing significantly through innovative basic research and successful clinical outcomes. This review explores our institutional experience, highlighting clinical cases and groundbreaking preclinical research within our comprehensive VCA program.
Keywords: vascularized composite allotransplantation; immunosuppression; tolerance induction; hand transplantation